Taxonomy and phylogeny of the Japanese species of the genus Dasycerus Brongniart (Coleoptera: Staphylinidae: Dasycerinae) with description of a new species and notes on D. poseidon Hu & Liang - Hashizume, Takuto; Maruyama, Munetoshi (Zootaxa, 2022)
Dasycerus occultus Hashizume & Maruyama, sp. nov. is described and illustrated based on specimens from Japan (Honshu and Kyushu). The holotype of D. japonicus Nakane, 1963 was revisited. The “D. japonicus” illustrated by Löbl & Calame (1996) was found not to be D. japonicus but rather to be D. occultus sp. nov. The discussion also includes D. poseidon Hu & Liang, 2021 from Taiwan. The phylogenetic relationships of this genus from Japan based on mitochondrial DNA sequences are discussed.